2010
DOI: 10.1586/erc.10.78
|View full text |Cite
|
Sign up to set email alerts
|

Aging and hypertension

Abstract: Aging is known to be a dominant risk factor in the progression of hypertension. Thus, accompanied by an increasing mean age of the population in developed countries, prevention and management of hypertension in the elderly is a task of pressing urgency. Age-associated blood pressure elevation is a result of the aging process in organ systems, which play a key role in the regulation of blood pressure. In addition, advanced aging of the cardiovascular system contributes to the presence of a varied phenotype in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“…Age is a powerful risk factor for the development of hypertension 28 . Management of age-associated hypertension may be a key issue in the prevention of cardiovascular events 29 . Gender differences have been shown in the management of hypertension 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Age is a powerful risk factor for the development of hypertension 28 . Management of age-associated hypertension may be a key issue in the prevention of cardiovascular events 29 . Gender differences have been shown in the management of hypertension 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Increasing age is a risk factor for hypertension, 39 preeclampsia, 40 and CVD 41 To assess whether the pregnancy-induced cardiac hypertrophy in Corin KO mice also worsens with age, we performed similar experiments in mice mated at 6 months of age. Compared to age-matched virgin Corin KO controls, Corin KO mice had a 20 ± 3% increase in HW/TL at GD18.5 (7.08 ± 0.20 vs. 8.51 ± 0.28 mg/mm, P=0.0003; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with increased incidence of CVD, preeclampsia, and peripartum cardiomyopathy in older pregnant women. 3941, 51 This is particularly relevant as the average age of pregnancy continues to rise. 52 We also showed that Corin KO mice had increased HW/TL and CD that persisted at least 28 days postpartum.…”
Section: Discussionmentioning
confidence: 99%
“…These ageassociated systemic changes strongly contribute to BP elevation. In addition, advanced aging of the cardiovascular system presents a varied phenotype in older adult hypertension (see "Vascular Diseases of Aging," "Cardiovascular Response," Cardiovascular System," "Hypertensive Cardiovascular Diseases"), such as nocturnal hypertension, white coat hypertension, and morning hypertension (Fukutomi and Kario 2010).…”
Section: Advanced Agesmentioning
confidence: 99%